2016
DOI: 10.1038/cr.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

Identification of blood vascular endothelial stem cells by the expression of protein C receptor

Abstract: Vascular growth and remodeling are dependent on the generation of new endothelial cells from stem cells and the involvement of perivascular cells to maintain vessel integrity and function. The existence and cellular identity of vascular endothelial stem cells (VESCs) remain unclear. The perivascular pericytes in adult tissues are thought to arise from the recruitment and differentiation of mesenchymal progenitors during early development. In this study, we identified Protein C receptor-expressing (Procr+) endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
119
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 57 publications
9
119
1
Order By: Relevance
“…Thus, this study provided strong evidence for the contribution of Sca1 + ‐VPCs to vascular injury repair and angiogenesis in ischemic tissues. Using different cell surface markers, different groups have identified different types of vessel wall‐resident stem/progenitor cells that contribute to neo‐angiogenesis . In this study, we have demonstrated that 7A was essential for neo‐angiogenesis in response to vascular injury.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, this study provided strong evidence for the contribution of Sca1 + ‐VPCs to vascular injury repair and angiogenesis in ischemic tissues. Using different cell surface markers, different groups have identified different types of vessel wall‐resident stem/progenitor cells that contribute to neo‐angiogenesis . In this study, we have demonstrated that 7A was essential for neo‐angiogenesis in response to vascular injury.…”
Section: Discussionmentioning
confidence: 67%
“…New endothelium in physiologic angiogenesis is thought to arise principally from local EC 67 , and circulating endothelial progenitors do not contribute to new endothelium in immunized LN 4 . Prior studies have highlighted multipotent vessel-resident EC progenitor populations in large vessels 68,69 and lung 70 and precursors in developing bone 71 that can differentiate into diverse EC phenotypes. CRP appear distinct from these populations: They lack Bst1 and Procr , markers of resident endothelial progenitors described in large vessels of liver 68 and fat pad 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Mice carrying a variant of EPCR with impaired ability to bind PC/aPC are viable without reported placental thrombosis and intrauterine death 17 . Though most well studied for their role in anticoagulation, new roles of aPC and EPCR in stem cell function [18][19][20][21][22] , inflammation [23][24][25] and immunity 26,27 have recently emerged. Thus, the mechanism of placental failure and whether it is primarily mediated by the loss of anticoagulation by EPCR remains unclear.…”
Section: Introductionmentioning
confidence: 99%